2019
DOI: 10.1126/science.aay3038
|View full text |Cite
|
Sign up to set email alerts
|

Realizing the potential of digital development: The case of agricultural advice

Abstract: The rapid spread of mobile phones creates potential for sustainably raising agricultural productivity for the 2 billion people living in smallholder farming households. Meta-analyses suggest that providing agricultural information via digital technologies increased yields by 4% and the odds of adopting recommended inputs by 22%. Benefits likely exceed the cost of information transmission by an order of magnitude. The spread of GPS-enabled smartphones could increase these benefits by enabling customized informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(159 citation statements)
references
References 62 publications
2
151
0
6
Order By: Relevance
“…There are more applications for small-scale farmers generally 38 but there is limited evidence to apply these interventions even outside of water scarce regions. For example, a meta-analysis carried out in 2019 only found five studies with nine observations that examined digital solutions that improved small-scale farmers' yields (researchers found a 0-8% increase) and the odds of adopting a recommended agricultural input (researchers found a 13-31% increase) 38 . While the goal of our systematic map was not to identify studies suitable for a meta-analysis, we found seven studies that examined digital solutions for farmers in water scarce regions.…”
Section: Discussionmentioning
confidence: 99%
“…There are more applications for small-scale farmers generally 38 but there is limited evidence to apply these interventions even outside of water scarce regions. For example, a meta-analysis carried out in 2019 only found five studies with nine observations that examined digital solutions that improved small-scale farmers' yields (researchers found a 0-8% increase) and the odds of adopting a recommended agricultural input (researchers found a 13-31% increase) 38 . While the goal of our systematic map was not to identify studies suitable for a meta-analysis, we found seven studies that examined digital solutions for farmers in water scarce regions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these opportunities, numerous digital services have been developed in recent years to improve smallholder farmers' access to agricultural information (Baumüller, 2018;Fabregas, Kremer, & Schilbach, 2019). Many existing solutions focus on supporting specific transactions along the value chain, such as providing market prices through SMS (Batchelor, Scott, Manfre, & Edwards, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, the lack of investments and fixed costs of new technologies can constrain the use of digital tools and games in agriculture in less developed regions. Nonetheless, 70 percent of the poorest 20 percent in low and middle-income countries have access to a mobile phone, and one in three people have internet access [72][73][74]. Although connectivity prevails in urban settings, it has spread to rural areas, where the ratio of farmers to extension workers exceeds 1000 to one [65,[72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, 70 percent of the poorest 20 percent in low and middle-income countries have access to a mobile phone, and one in three people have internet access [72][73][74]. Although connectivity prevails in urban settings, it has spread to rural areas, where the ratio of farmers to extension workers exceeds 1000 to one [65,[72][73][74]. And with increased physical restrictions from COVID-19, there is a need to reach and engage with farmers using innovative technologies.…”
Section: Discussionmentioning
confidence: 99%